Identification of Pseudo-Random Noise Generator Structure - Lossmann, E.; Meister, A.; Madar, U. (Elektronika ir Elektrotechnika, 2005)
Pseudorandom sequences of maximal length (m-sequences) needed in many telecommunication applications can be generated using algebraic methods and generating matrix for large extended Galois’ finite array GF(2m). If we know the sequence of symbols during one period the generating polynomial of a m-sequence is fully identifiable. The task of identification is further analyzed in two parts: identification of the coefficients of minimal polynomial Gβ (z) = Mβ (z) , and generation of identical sequence to the given msequence. To identify the coefficients of generating minimal polynomial of the m-sequence it is sufficient to know the sequence of 2m symbols. MATLAB programs for both tasks have been compiled and investigated. One possible solution to generate the identical partial m-sequence is to generate the partial m-sequences of length 2m if we know the value of m. The value of i for the partial sequence x[i, k ] should be chosen according to the maximum of non-periodic correlation coefficients. Bibl. 3 (in English; summaries in Lithuanian, English and Russian).